Digital health care service reform and health inequity for older people: a quasi-natural experiment in China - Qi, Xinzhu; Feng, Tieying; Deng, Renyi (Frontiers in Public Health, 2023)
Objective: Addressing health inequity (HI) for older people is a pivotal global public health concern, as it impedes the process of healthy ageing. The digital health care service reform (DHSR) emerges as a progressive public health approach to enhance the health and well-being of older adults by providing comprehensive and equitable medical services. This study elucidates the association between DHSR and HI for older individuals to augment comprehension of DHSR implementation.The initiation of the action plan for smart health and eldercare (SHE) in 2017 serves as a quasi-natural experiment. Utilizing data from the China Health and Retirement Longitudinal Study (CHARLS) in 2015 and 2018, a propensity score matching (PSM) method was used to select samples, and a difference-in-differences (DID) regression was used to ascertain the net effect of DHSR on HI for older individuals in China. This methodology mitigates selection bias and segregates the DHSR effect from temporal shifts or other occurrences.The PSM-DID analysis reveals that DHSR reduced the HI index for older individuals by 0.301 (p<0.001). Heterogeneity analyses indicate that the effect of DHSR was more pronounced in older males (-0.333, p<0.001) than females (-0.251, p<0.005). The impact of DHSR was notably higher for older population in the western (-0.557, p<0.001) and central regions (-0.318, p<0.005) compared to the eastern region, where the relationship was statistically non-significant.The results demonstrate that DHSR plays a vital role in diminishing HI, fostering inclusive growth in public health. The study underscores the imperative of sustained DHSR endeavours and allocating resources to key older demographics to substantially mitigate HI.